FAST Observations of FRB 20220912A: Burst Properties and Polarization Characteristics - Zhang, Yong-Kun; Li, Di; Zhang, Bing; Cao, Shuo; Feng, Yi; Wang, Wei-Yang; Qu, Yuanhong; Niu, Jia-Rui; Zhu, Wei-Wei; Han, Jin-Lin; Jiang, Peng; Lee, Ke-Jia; et al. (The Astrophysical journal, 2023)
We report the observations of FRB 20220912A using the Five-hundred-meter Aperture Spherical radio Telescope. We conducted 17 observations totaling 8.67 hr and detected a total of 1076 bursts with an event rate up to 390 hr −1 . The cumulative energy distribution can be well described using a broken power-law function with the lower- and higher-energy slopes of −0.38 ± 0.02 and −2.07 ± 0.07, respectively. We also report the L -band (1–1.5 GHz) spectral index of the synthetic spectrum of FRB 20220912A bursts, which is −2.6 ± 0.21. The average rotation measure value of the bursts from FRB 20220912A is −0.08 ± 5.39 rad m −2 , close to 0 rad m −2 and was relatively stable over 2 months. Most bursts have nearly 100% linear polarization. About 45% of the bursts have circular polarization with Signal-to-Noise ratio > 3, and the highest circular polarization degree can reach 70%. Our observations suggest that FRB 20220912A is located in a relatively clean local environment with complex circular polarization characteristics. These various behaviors imply that the mechanism of circular polarization of FRBs likely originates from an intrinsic radiation mechanism, such as coherent curvature radiation or inverse Compton scattering inside the magnetosphere of the FRB engine source (e.g., a magnetar).